Keynote Address - Shuman, Jill (MD Conference Express, 2015)
Nutrition support professionals are responsible for maintaining the integrity of the gut mucosa. Coaching and teaching can be accomplished with electronic tools and apps. It may be possible to grow stem cells into intestinal tissue that can be transplanted back to patients without inducing immunocompromise. Pooling international data can improve patient outcomes.